Nonfinancial Consequences of Identity Theft Revisited: Examining the Association of Out-of-Pocket Losses With Physical or Emotional Distress and Behavioral Health - Maher, Cooper A. (Criminal justice and behavior, 2024)
The study investigates whether nuanced measures of financial loss are associated with physical and/or emotional distress relating to one’s identity theft victimization. A subsample of victims of identity theft from the National Crime Victimization Survey (NCVS) Identity Theft Supplement (n = 1,557) was examined. Financial loss was considered as the total amount lost, whether victims suffered any financial losses, and whether losses were in the 95th percentile. Stepwise negative binomial and logistic regressions were estimated for physical and emotional distress and behavioral health outcomes (i.e., both physical and emotional distress). Findings indicate that out-of-pocket losses were substantively associated with physical and emotional distress as well as behavioral health outcomes only when considering nuanced measures of monetary loss. Time taken to resolve identity theft was associated with increased distress across all outcomes. Nonfinancial consequences of identity theft are fundamentally different phenomena than financial loss and indicate the need for multifaceted responses which acknowledge these outcomes.